Lectotypification of fifteen names of Rubus L. (Rosaceae) mainly from the Hengduan Mountains, China - Xiong, Xianhua; Li, Meng; Liang, Tongjun; Ju, Wenbing; Xu, Bo; Zhang, Li; Gao, Xinfen (Phytotaxa, 2019)
Rubus Linnaeus (1753: 492), one of the most taxonomically challenging genera in Rosaceae (Lu 1983, Alice & Campbell 1999, Alice et al. 2008), comprises more than 700 species (Lu & Boufford 2003) and is distributed across the world except Antarctica (Alice & Campbell 1999). The Hengduan Mountains, the mountains at the eastern end of the Himalayas, are widely regarded as a global biodiversity hotspot. During a taxonomic revision of Rubus L. in the Hengduan Mountains and its neighbouring regions, we found that fifteen names have never been typified. Lectotypification of these names are designated here after examination of previous works (Zandee & Kalkman 1981, Kalkman 1984 & 1987, Monasterio-Huelin & Castroviejol 1993, Monasterio-Huelin 1996, Monasterio-Huelin & Webert 1996, Bean 1997a & b, Allen 1998, Widrlechner 1998, Matzke-Hajek 2001a & b, Sennikov & Weber 2010, Deng 2015, Weber 2015a & b, Gupta et al. 2016, Yang et al. 2016, Beek et al. 2017, Dash & Gupta 2017, Király 2017, Király et al. 2017).